Portal pengetahuan sebagai pusat aset pengetahuan : pelaksanaan pengurusan pengetahuan di sektor awam - Mohamad, Taufik (2003)
Changing of the national economy from industrial based to knowledge based has promoted the needs to increase the knowledge, skill and expertise in the organizations. Knowledge is the key driver of the economy growth to be more competitive in generating the country wealth. In public sector, knowledge plays an important role in K-Economy which it focuses on increasing the quality of public services and implementing the sector's responsibility towards the society. These sectors need to have a knowledge management system as a new paradigm of management in managing the knowledge asset with more effectively and innovatively. This knowledge management will produce valuable information and ready to be used by the organization in giving the best services and systematic to the customer. It will involve the process of changing the information into knowledge by means using of a technology support which called Knowledge Management System. This system is a web based system specifically a portal. This portal contains four important component which is content, community technology and process. Today, most public sectors still using a static website, therefore the process of knowledge sharing couldn't be implemented. By using this system, valuable knowledge assets can be centralized which it can be used to assists the public sector to achieve their objectives in providing the best services and increasing the country economic growth.